(untitled) (ELS Journal on Interdisciplinary Studies in Humanities, 2022)
This research aims to identify the dominating deixis among the many types of deixis in Jeremy Zucker’s songs "You Were Good to Me" and "Comethru." Deixis is derived from the classical Greek phrase "to exhibit, to point out." Deixis is the study of interpreting the relationship of a situation with words, phrases, and elements expressed in a sentence. This study used a qualitative descriptive approach. According to the research, 58 words in the song "You Were Good to Me" feature various types of deixis, and 54 words in the song "Comethru." Person deixis points to objects, all pronouns, and possessives. Spatial deixis is used to indicate a location, whereas Temporal deixis is used to indicate a time.